Electrohydrodynamic Jet Printing Driven by a Triboelectric Nanogenerator. (1st April 2019) - Wu, Changsheng; Tetik, Halil; Cheng, Jia; Ding, Wenbo; Guo, Hengyu; Tao, Xingtian; Zhou, Nanjia; Zi, Yunlong; Wu, Zhiyi; Wu, Huixuan; Lin, Dong; Wang, Zhong Lin
Abstract: Electrohydrodynamic jet (e‐jet) printing is a high‐resolution printed electronics technique that uses an electric field to generate droplets. It has great application potential with the rapid development of flexible and wearable electronics. Triboelectric nanogenerators (TENG), which can convert mechanical motions into electricity, have found many high‐voltage applications with unique merits of portability, controllability, safety, and cost‐effectiveness. In this work, the application of a TENG is extended to printed electronics by employing it to drive e‐jet printing. A rotary freestanding TENG is applied as the high‐voltage power source for generating stable ink droplet ejection. The TENG‐driven droplet generation and ejection process and printed features with varied operation parameters are investigated. Results reveal that the jetting frequency could be controlled by the TENG's operation frequency, and high‐resolution printing with feature size smaller than nozzle size is achieved using the setup. Notably, TENG as the power source for e‐jet printing supplies a limited amount of current, which leads to better safety for both equipment and personnel compared to conventional high‐voltage power supplies. With the superiority of TENG in the sense of safety and cost, the work presents a promising solution for the next‐generation of high‐resolution printed electronics and broadens the scope of TENG application. Abstract : An alternative way of driving electrohydrodynamic jet printing by using a triboelectric nanogenerator (TENG) as the high voltage power source is reported. The droplet jetting process driven by a TENG and effects of operation parameters on printed features are investigated. This work presents a promising solution for the next generation of high‐resolution printed electronics with merits of enhanced safety and low cost.